Hayabusa – animated short film production report - Goh, Jared Rui Jie (Nanyang Technological University, 2024)
Report documenting the production of the animated music video Hayabusa, from the perspective of director and lead animator Jared Goh. Hayabusa is the Final Year Project of Jared Goh, Yang Quanhui and Noel Tay.